Diagnostics and treatment of biliary dyskinesia: clinical guidelines of the Russian gastroenterological Association - V. T. Ivashkin; I. V. Mayev; Yu. O. Shulpekova; Ye. K. Baranskaya; A. V. Okhlobystin; A. S. Trukhmanov; T. L. Lapina; A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of publication. To present the guidelines on diagnostics and treatment of biliary dyskinesia to practical doctors. Summary. The gallbladder dyskinesia and sphincter of Oddi dyskinesia are defined as the diseases of functional origin caused by motility and visceral sensitivity disorders. The pathogenesis of these disorders is not completely understood. Development of sphincter of Oddi dysfunction is related to previous cholecystectomy. Contractility disorders along with increased lithogenicity followed by cyclooxygenase-2 overactivation in biliary tract tissue play significant pathogenic role; putative change in bile acid composition may be involved as well. Diagnosis of biliary dyskinesia requires first the careful analysis of pattern of pain and compliance of symptoms to biliary pain criteria; second, instrumental tests that exclude organic origin of biliary disease. Estimation of the type of biliary dysfunction is established on compliance of the detected symptoms to proposed criteria. Conclusion. Biliary dyskinesia pathogenesis is not studied well. Development of attacks of biliary pain (according to established criteria) and lack of organic disorders evidence, may help to suspect the presence of biliary dyskinesia. To exclude organic biliary diseases with confidence, informative modern diagnostic tests of biliary tract visualization should be applied. Therapeutic approach should include correction of diet and lifestyle modification, administration of antispasmodic medications and agents modulating the state of nervous system, in selected cases the option of papillosphincterotomy should be considered.